The Role of Service Recovery in Post-purchase Consumer Behavior During COVID-19: A Malaysian Perspective - Mazhar, Muhammad; Ting, Ding Hooi; Hussain, Ali; Nadeem, Muhammad Aamir; Ali, Muhammad Asghar; Tariq, Umaima (Frontiers in Psychology, 2022)
The purpose of this study is to investigate the incidence of service failure in rendering service process during COVID-19. It further explores the outcomes of service recovery offered to customers in case of service failure. Like other businesses, webstores have also faced the challenges in their efforts to satisfy their customers during COVID-19. Service failure has increased due to unexpected circumstances produced by this pandemic. It has become necessary for the webstores to retain their dissatisfied customers by reconsidering their service strategies. Relevant data for the purpose of this study was collected through questionnaires from 383 respondents by using online channels. The online channels were exclusively employed for maintaining the safety of respondents during COVID-19. Respondents for this study were online shoppers who encountered service failure during COVID-19. The results indicated that the incidence of service failure has increased due to an increase in online shopping during COVID-19. Some customers tend to repurchase from the same webstore. On the other hand, some customers do not want to purchase again from same seller and decided to switch to the alternative webstore. Based on the findings, new strategy for online shopping service providers was introduced. This strategy will be helpful for the online service providers to increase their profitability by retaining their dissatisfied customers. Service providers can minimize the number of customers switching to other webstores by reducing the events of service failure. Customer assistive intent can also be helpful for service providers to increase the efficiency of service recovery. Conducting a proper follow up after providing service recovery can also reduce the switching of customer. It will be helpful for service providers to understand the customers expectations before recovery process and their feeling after getting service recovery.